Timetable Optimization for Utilization of Regenerative Braking Energy: A Single Line Case over Istanbul Metro Network - Demirci, Ibrahim Ethem; Celikoglu, Hilmi Berk (IEEE, 2018)
Energy costs still have a large proportion in operational expenses in metro lines, even though metro is the least energy-consuming mode of transport. Recently, researchers have shown an increased interest in the utilization of regenerative braking energy (RBE) to reduce the energy consumption: synchronizing the accelerating and braking trains is one of the more practical ways of the utilization of RBE. In this paper, a timetable optimization model is proposed to pair the accelerating and breaking trains in the operation to enhance the utilization of RBE. The main objective of the model proposed is to provide maximum total overlapping time between breaking and accelerating periods of trains by adjusting the timetable. In comparison with the existing methods, the proposed timetable optimization model requires less modeling information and calculates more train in cooperation. A case study over Istanbul Metro M4 line is studied employing a Genetic Algorithm to real operating data. The simulation results confirm the effectiveness of the proposed method that the total overlapping time has increased to a considerable extent in different headway scenarios.